Consumer debt - Tardiff, Joseph C. , 1966- (Current controversies, 2010)
Editorial Reviews: VOYA: Laura Panter -- The "Current Controversies" series explores the social, political and economic controversies that are plaguing world today. Each chapter begins with a preface that offers background information on the topic at hand. The chapters are organized around key questions that are answered by various authors with differing opinions. The opinions of the authors of each article are those that could be found in our every day society. Consumer Debt delves into the increasing burden of debt that middle class and lower income individuals are accumulating through credit cards, school loans, and high house mortgages. Expenses continue to increase as income levels remain stagnant or decrease. For individuals of the Gen Xer age, expenses are so high that saving for retirement for is, for most, unattainable. Credit card companies hit users with high interest rates and hidden fees while other arguments counter that there are plenty of consumers who do not use credit at all. This series is mainly designed for controlled research through information gleaned from periodicals, newspapers, books, government documents and organizations; however, the drawback is that most information contained in these books is already over a year old. More accurate information can be found through databases and online research. This would be a good purchase for libraries if students needed older statistics to back up their position while writing a research paper. Reviewer: Laura Panter